Perbandingan Efek Mengkudu Fermentasi 1 Tahun dan 2 Tahun Terhadap kadar Il-6 pada Tikus Wistar - Faradita Nur Fatikha (Fakultas Kedokteran, 2026)
Background: Interleukin-6 is a key cytokine involved in inflammatory processes and immune regulation, serving as an important biomarker of immune system activity. Elevated IL-6 levels are commonly observed during inflammation. Morinda citrifolia L. (noni) contains various bioactive compounds, including flavonoids, iridoids, polysaccharides, and scopoletin, which exhibit immunomodulatory properties. Fermentation may alter the profile and bioavailability of these compounds, potentially affecting their biological activity. However, the influence of fermentation duration on the immunomodulatory effects of fermented noni remains limited. Aim: This study aimed to compare the effects of noni fermented for 1 year and 2 years on serum IL-6 levels in Wistar rats induced with inflammation. Methods: This study employed a true experimental design with a post-test only control group. Twenty-four male Wistar rats were randomly divided into four groups: negative control (0.5% CMC-NA), positive control (Echinacea purpurea extract), noni fermented for 1 year, and noni fermented for 2 years. Inflammation was induced using intravenous India ink. After treatment, serum IL-6 levels were measured using the Enzyme-Linked Immunosorbent Assay (ELISA). Data were analyzed using one-way ANOVA followed by post hoc Tukey HSD test. Results: All groups exposed to inflammatory induction showed increased IL-6 levels. The highest IL-6 concentration was observed in the group receiving noni fermented for 2 years. Statistical analysis revealed a significant difference in IL-6 levels among groups (p < 0.05). Conclusion: Longer fermentation duration of Morinda citrifolia L. enhances its immunomodulatory activity, as indicated by increased IL-6 levels during inflammatory response. These findings suggest that fermentation time plays a crucial role in modulating the biological effects of fermented noni.
:: Finalisasi repositori 13 Agustus 2026_Kurnadi
Keywords: Morinda citrifolia L.; fermented noni; Interleukin-6; Inflammation